Evaluasi Kinerja Pelayanan Air Bersih PDAM âTirto Panguripanâ Kabupaten Kendal Periode 2009-2011 - , MAYA PUSPITA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Healthy water is one of the basic necessities for human life. Therefore the water must be available in sufficient quantity and quality. Need for clean water for various purposes such as households and industry will continue to increase over time in line with the rate of builders in various sectors as well as the population continues to grow. On the other hand, the amount of clean water supply and existing infrastructure is still relatively limited so it cannot meet all of these needs PDAM has a concrete goal, namely social goals and economic goals. PDAM goal-oriented social usefulness and value of water services to the community, while the goal is the ability to improve the economy taps the company's contribution to revenue (PAD). In this thesis, the author choose the title of Evaluasi Kinerja Pelayanan Air Bersih PDAM âTirto Panguripanâ Kabupaten Kendal Periode 2009-2011. The purpose of this study is to determine the constraints faced by PDAM "Tirto Panguripan" Kendal so have not been able to provide maximum service to the surrounding community and the local government, so that the research is expected to contribute ideas, especially in an effort to determine the right strategy for optimize the performance and management of PDAM "Tirto Panguripan" Kendal that PDAM "Tirto Panguripan" Kendal can provide maximum service to serve the needs of water for entire population in the district as well as improve contribution towards Kendal revenue reached USD 11 billion by optimizing potential has not been fully exploited. The data in this study were obtained from the financial statements for 3 years, ie from 2009 to 2011. This research uses the case study method, the data collection techniques in the form of documentation, interviews, and review of the literature. Based on the evaluation of the soundness of PDAM "Tirto Panguripan" Kendal based Kepmendagri No. 47 Year 1999, the health of PDAM Tirto Panguripan Kendal in 2009 quite well with the performance value of 66.66